Let's solve the equation step by step.
You started with the equation:
\[ \frac{2}{3} - 4x + \frac{7}{2} = -9x + \frac{5}{6} \]
-
Combine like terms on the left side:
- First, find a common denominator for \(\frac{2}{3}\) and \(\frac{7}{2}\). The common denominator is 6.
- Rewrite the fractions: \[ \frac{2}{3} = \frac{4}{6} \quad \text{and} \quad \frac{7}{2} = \frac{21}{6} \]
- Now combine: \[ \frac{4}{6} + \frac{21}{6} = \frac{25}{6} \]
- So the equation becomes: \[ \frac{25}{6} - 4x = -9x + \frac{5}{6} \]
-
Move all terms involving \(x\) to one side and the constant terms to the other side:
- Add \(9x\) to both sides: \[ \frac{25}{6} - 4x + 9x = \frac{5}{6} \]
- This simplifies to: \[ \frac{25}{6} + 5x = \frac{5}{6} \]
-
Isolate the term with \(x\):
- Subtract \(\frac{25}{6}\) from both sides: \[ 5x = \frac{5}{6} - \frac{25}{6} \]
- This simplifies to: \[ 5x = \frac{5 - 25}{6} = \frac{-20}{6} = \frac{-10}{3} \]
-
Solve for \(x\):
- Divide both sides by 5: \[ x = \frac{-10}{3} \div 5 = \frac{-10}{3} \cdot \frac{1}{5} = \frac{-10}{15} = \frac{-2}{3} \]
So the solution is:
\[ \boxed{x = -\frac{2}{3}} \]